2017
DOI: 10.3389/fmicb.2017.00378
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Herbicide Triasulfuron on Soil Microbial Community in an Unamended Soil and a Soil Amended with Organic Residues

Abstract: The effect of organic amendments and pesticides on a soil microbial community has garnered considerable interest due to the involvement of microorganisms in numerous soil conservation and maintenance reactions. The aim of this work was to assess the influence on a soil microbial community of the simultaneous application of the herbicide triasulfuron at three doses (2, 10, and 50 mg kg-1), with an organic amendment [sewage sludge (SS) or green compost (GC)]. Dissipation kinetics, soil microbial biomass, dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…The DT 50 values found in this study are within the range observed in other field studies on unamended soils (< 50 days) (Sarmah et al, 2000;EFSA, 2015), but they are lower than those obtained in laboratory experiments (33-76 days) (James et al, 1999;EC, 2000;Pose-Juan et al, 2017). Mobility into deeper layers was one the factors proposed for trisulfuron increased dissipation in the field.…”
Section: Triasulfuron Dissipationsupporting
confidence: 74%
See 2 more Smart Citations
“…The DT 50 values found in this study are within the range observed in other field studies on unamended soils (< 50 days) (Sarmah et al, 2000;EFSA, 2015), but they are lower than those obtained in laboratory experiments (33-76 days) (James et al, 1999;EC, 2000;Pose-Juan et al, 2017). Mobility into deeper layers was one the factors proposed for trisulfuron increased dissipation in the field.…”
Section: Triasulfuron Dissipationsupporting
confidence: 74%
“…The results indicating the increased DT 50 values of triasulfuron in the GCamended soil are in agreement with the adsorption coefficients K d of triasulfuron for the soil+GC (0.53 mL g -1 ) (Table S3, in Supplementary material), and higher than in the unamended soil (0.05 mL g -1 ). An increased adsorption of this herbicide by soils amended with different composted organic residues has also been reported in laboratory studies (Said-Pullicino et al, 2004;Pose-Juan et al, 2017). However, the addition of straw residues as organic amendment increased the dissipation of triasulfuron in lab experiments, but not in the field (Menne and Berger, 2001).…”
Section: Triasulfuron Dissipationsupporting
confidence: 58%
See 1 more Smart Citation
“…Global pesticide production increases every year by about 11%, with herbicides, insecticides and fungicides dominating in the sales structure (Carvalho 2017). Long-term and intensive application of these agents can lead to extensive treated of soil ecosystems (Pose-Juan et al 2017). As Ye et al (2018) reports, even 80-90% of applied pesticides penetrate into the natural environment, and only a small percent (1-2%) operate against the target organisms, while the remaining share (10-20%) is situated on the plant surface.…”
Section: Introductionmentioning
confidence: 99%
“…As Ye et al (2018) reports, even 80-90% of applied pesticides penetrate into the natural environment, and only a small percent (1-2%) operate against the target organisms, while the remaining share (10-20%) is situated on the plant surface. This can have a harmful effect on the quantity and quality of microorganisms inhabiting the soil, as well as on their physiological processes, which is related to unfavourable changes in soil productivity and fertility (Pose-Juan et al 2017). It is very important to determine the response of microorganisms and soil enzymes to pesticides in soil in view of their participation in biogeochemical cycles and their role in maintaining proper soil functions and promoting growth and development of plants (Grz¹dziel andGa-³¹zka 2018, Siwek-Ziomek andKoper 2018).…”
Section: Introductionmentioning
confidence: 99%